The Comparative Study Showing of the Effect of Telmisartan and Ramipril on Diabetic Profile in Hypertensive Pre-Diabetic Patients - Abdullah Ansari; Ayesha Raoof (Technological Innovation in Pharmaceutical Research Vol. 8, 2021)
Background: Hypertension, a common cardiovascular disease, is being increasingly associated with other co-morbid conditions like Diabetes mellitus, worsening its outcome. Both telmisartan and ramipril are effective anti hypertensive agents. The present study compares the efficacy of telmisartan and ramipril in controlling or preventing the progression of pre-diabetes to diabetes in stage 1 hypertensive patients. It also aims at assessing the effect of Telmisartan and Ramipril on FBS and HbA1C over 12 months treatment period in males and females and compare it. Methods: A prospective, randomised, single centre, comparative observational study is conducted over a period of 12 months on stage 1 hypertensive patients with pre-diabetes. 60 patients are recruited and randomised into two treatment groups. They received the assigned drug for a period of 12 months and are followed up. At each visit, blood pressure was measured and diabetic profile was tested. Results: This study showed that both telmisartan and ramipril controlled the blood pressure effectively. Telmisartan controlled the progression of fasting blood sugar and glycosylated haemoglobin better than ramipril in stage 1 hypertensive patients with pre diabetes. Conclusions: Both telmisartan and ramipril were affecting in controlling the blood pressures. Telmisartan has a statistically significant effect in preventing the progression of prediabetes to diabetes mellitus in stage 1 hypertensive patients with pre diabetes when compared with ramipril.